2019
DOI: 10.4317/jced.56194
|View full text |Cite
|
Sign up to set email alerts
|

Oral and maxillofacial lesions in older individuals and associated factors: A retrospective analysis of cases retrieved in two different services

Abstract: BackgroundStudies on the oral and maxillofacial lesions (OMLs) in older people usually assess data of laboratory services and data from oral medicine clinic have been poorly described. The aim of this study was to describe and to compare OMLs in older individuals considering two data sources, besides to assess associated factors with the three most frequent lesions.Material and MethodsA retrospective study was conducted with individuals aged 60 years or older. Data of individuals and lesions reported in both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 24 publications
0
6
1
2
Order By: Relevance
“…The aging population is becoming a public health concern, especially in developing countries 17 . The elderly are susceptible to noncommunicable diseases, including those involving the orofacial region 1 , 2 , 17 . In this group, the vulnerability to orofacial diseases may be attributed to aging-related changes in the tissues and the immune response 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aging population is becoming a public health concern, especially in developing countries 17 . The elderly are susceptible to noncommunicable diseases, including those involving the orofacial region 1 , 2 , 17 . In this group, the vulnerability to orofacial diseases may be attributed to aging-related changes in the tissues and the immune response 18 .…”
Section: Discussionmentioning
confidence: 99%
“…With aging, an individual becomes vulnerable to several diseases including those involving the orofacial region 1 , 2 . This vulnerability to orofacial lesions has led to a rise in interest in the oral health of this population and hence an increase in epidemiological surveys in this age group 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Contradictory results by other studies were also found presenting the greatest number of inflammatory lesions. 25,26 Among all biopsies, a wide variety of benign lesions were recognized. The most frequent was goiter (60%), common in the age range of 41-50 years with female predominance.…”
Section: Discussionmentioning
confidence: 99%
“…Percebeu-se que a HFI teve acometimento em diversos sítios da cavidade oral, sendo que a mucosa jugal e o palato duro foram os mais prevalentes. Em seguida, o carcinoma espinocelular foi a segunda lesão mais frequente, semelhante ao que foi encontrado por Fonseca et al 25 .…”
Section: Materials E Métodounclassified
“…A presença de lesões potencialmente malignas como: leucoplasia (5,96 %), queilite actínica (2,55%) e eritroplasia (0,85%) diagnosticadas com a presença ou não de displasia epitelial, ressalta a importância do acompanhamento pelo cirurgião dentista e colaboração do paciente para um melhor prognóstico do tratamento. Neste estudo, a leucoplasia configura entre as três lesões mais frequentes, concordando com Rohini et al 11 e Fonseca et al 25 . Esta lesão cancerizável muitas vezes não é detectada ou a biópsia é negligenciada e em grande parte desses casos podem evoluir para um carcinoma.…”
Section: Materials E Métodounclassified